2010
DOI: 10.1158/1535-7163.mct-09-0663
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Resistance Protein and P-glycoprotein Limit Sorafenib Brain Accumulation

Abstract: Sorafenib is a second-generation, orally active multikinase inhibitor that is approved for the treatment of patients with advanced renal cell carcinoma and patients with unresectable hepatocellular carcinoma. We studied active transport of sorafenib in MDCK-II cells expressing human P-glycoprotein (P-gp/ABCB1) or ABCG2 (breast cancer resistance protein) or murine Abcg2. Sorafenib was moderately transported by P-gp and more efficiently by ABCG2 and Abcg2. Because sorafenib is taken orally, we orally administere… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
124
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(132 citation statements)
references
References 35 publications
8
124
0
Order By: Relevance
“…However, most of them have been showed to be substrates of Pgp and/ or BCRP (29)(30)(31)(32)(33)(34), and are likely to exert their effects only in areas where the BBB or blood-tumor barrier is permeable, as described by Taskar and colleagues with lapatinib (35).…”
Section: Discussionmentioning
confidence: 99%
“…However, most of them have been showed to be substrates of Pgp and/ or BCRP (29)(30)(31)(32)(33)(34), and are likely to exert their effects only in areas where the BBB or blood-tumor barrier is permeable, as described by Taskar and colleagues with lapatinib (35).…”
Section: Discussionmentioning
confidence: 99%
“…Agarwal and colleagues reported that ABCG2 has higher affinity for sorafenib than ABCB1 and play a dominant role in the efflux of sorafenib at the BBB in vivo study (25). Lagas and colleagues confirmed that brain efflux of sorafenib is more efficiently transported by ABCG2 with playing the dominant role in limiting its brain accumulation by murine Abcg2 (26). Among these publications, none of them shows that sorafenib is an inhibitor of the ABCG2 transporter.…”
Section: Discussionmentioning
confidence: 99%
“…P-gp recognizes drugs with various structures and actions as its substrates (29), suggesting that it has an impact on the pharmacokinetics of a wide range of drugs, which include anticancer drugs, antiepileptic drugs, and immunosuppressive drugs, and that it may contribute to critical adverse events associated with these drugs (30,31). Indeed, several studies have indicated that bioavailability of paclitaxel (32), etoposide (ETP) (33), erlotinib (19), and sorafenib (34), all of which are anticancer drugs and P-gp substrates, are dramatically increased in mice with P-gp deficits after oral administration. Based on substantial evidence, P-gp is recognized as an extremely important factor in the regulation of the pharmacokinetics of drugs used in the clinic.…”
Section: Characterization Of P-gpmentioning
confidence: 99%
“…P-gp recognizes and transports a wide range of drugs, including a large number of anticancer drugs (29,34) and therefore influences their pharmacokinetics. Importantly, changes in the expression or functional activity of P-gp induced by anticancer drugs frequently causes high rates of multi-drug resistance in cancer cells (48) and also affects the disposition of various P-gp substrate drugs in normal tissues (1).…”
Section: Alteration In the Expression And Function Of P-gp Induced Bymentioning
confidence: 99%